Use of New Ultrasonography Methods for Detecting Neoplasms in Dogs and Cats: A Review - Ercolin, Anna Carolina Mazeto; Uchôa, Alex Silveira; Aires, Luiz Paulo Nogueira [UNESP]; Gomes, Diego Rodrigues; Tinto, Stefany Tagliatela; Feliciano, Giovanna Serpa Maciel; Feliciano, Marcus Antônio Rossi (MDPI, 2024)
The aim of this literature review was to present the novel imaging modalities elastography and contrast-enhanced ultrasonography. We provided an overview of the concepts and applications of each technique for the investigation of neoplastic and metastatic tumors in dogs and cats. Studies on elastography are based on the elasticity and deformation of the evaluated tissue. The information obtained from the different types of elastography can aid in the detection and differentiation of malignant and benign structures. Descriptions of elastography studies in several organs and tissue in veterinary medicine reported that, in general, malignant tumors tend to be more rigid and, therefore, less deformable than benign lesions or in comparison to the healthy parenchyma. Contrast-enhanced ultrasonography is based on the intravenous injection of contrast media constituted by microbubbles. This imaging modality can be performed in nonsedated animals and provides information on the tissue perfusion, allowing the investigation of macro- and micro-circulation. Studies on different organs and tissues were performed in dogs and cats and revealed a tendency of malignant tumors to present faster transit of the contrast media (time to wash-in, peak and wash-out). These advanced techniques can be associated with other imaging modalities, aiding important information to the well-established exams of B-mode and Doppler ultrasonography. They can be used as screening tests, potentially representing an alternative to the invasive sampling methods required for cytological and histopathological analysis.
Keywords: canine; contrast-enhanced ultrasound; elastography; feline; metastasis; neoplasia